Emotion dysregulation in hypochondriasis and depression. (26th April 2017) - Bailer, Josef; Witthöft, Michael; Erkic, Maja; Mier, Daniela
Abstract : Background: The aim of this study was to explore whether certain aspects of emotion dysregulation (i.e., facets of alexithymia and rumination) are more closely linked to hypochondriasis than to depression and vice versa. Methods: Nineteen patients with hypochondriasis (HYP), 33 patients with depression, and 52 healthy control participants completed the Toronto Alexithymia Scale, the Response Styles Questionnaire, and additional symptom and illness behaviour scales. A clinical interview was used to establish DSM‐IV diagnoses and to exclude all cases with more than one axis I diagnosis. Results: Depression patients reported more difficulties describing feelings and more symptom‐ and self‐focused rumination than both HYP patients and healthy individuals, whereas HYP patients differed only from healthy individuals in regard to more difficulties in identifying feelings and more symptom‐focused rumination. Multiple regression analyses, including all assessed facets of emotion dysregulation, showed that the degree of somatoform features (somatic symptoms, health anxiety, and illness behaviour) was specifically predicted by higher difficulties in identifying feelings scores, whereas depressive symptom levels were specifically predicted by higher rumination scores. Conclusions: Specific associations were found between difficulties in identifying feelings and key features of HYP, whereas depression was linked to a more generalized pattern of emotion regulation deficits. Key Practitioner Message: Emotion dysregulation can be found in hypochondriasis and depression Difficulties in identifying own feelings are specifically linked to somatic symptoms, health anxiety, and illness behaviour, whereas a more generalized pattern of emotion dysregulation is found in relation to depression Further research is needed to investigate whether the effectiveness of current treatments for depression, hypochondriasis, health anxiety, and related disorders could be improved by additional emotion regulation interventions